2022
DOI: 10.1161/circulationaha.122.058575
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Catheter Ablation Versus Antiarrhythmic Drug Therapy in Atrial Fibrillation: The CABANA Randomized Clinical Trial

Abstract: Background: In the CABANA trial (Catheter Ablation vs Antiarrhythmic Drug Therapy for Atrial Fibrillation), catheter ablation did not significantly reduce the primary end point of death, disabling stroke, serious bleeding, or cardiac arrest compared with drug therapy by intention-to-treat, but did improve the quality of life and freedom from atrial fibrillation recurrence. In the heart failure subgroup, ablation improved both survival and quality of life. Cost-effectiveness was a prespecified CABAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
(80 reference statements)
2
38
0
Order By: Relevance
“…Despite advances in ablation and procedure techniques, costeffectiveness analyses of ablation-based rhythm control therapy have yielded heterogeneous conclusion that depend on the analysis model, parameters derived from the literature, and study population (17,18,(35)(36)(37)(38)(39). Recently, Chew et al (18) reported randomized trialbased economic evaluation results suggesting that catheter ablation of AF is economically attractive compared with drug therapy with an ICER of $57,893/QALY using the conventional WTP threshold of $100,000/QALY in the US. This study included detailed and comprehensive resource use data and quality-of-life adjustment factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in ablation and procedure techniques, costeffectiveness analyses of ablation-based rhythm control therapy have yielded heterogeneous conclusion that depend on the analysis model, parameters derived from the literature, and study population (17,18,(35)(36)(37)(38)(39). Recently, Chew et al (18) reported randomized trialbased economic evaluation results suggesting that catheter ablation of AF is economically attractive compared with drug therapy with an ICER of $57,893/QALY using the conventional WTP threshold of $100,000/QALY in the US. This study included detailed and comprehensive resource use data and quality-of-life adjustment factors.…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that ablation-based rhythm control of AF is related to economic benefit. In some countries, economic assessments have reported a good cost-saving in ablation-based therapy compared with medical therapy ( 17 , 18 ). However, the economic evaluation of different rhythm control strategies for treating AF has not been conducted in the Republic of Korea.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the specific pathophysiological mechanism of AF, atrial arrhythmias still recur in 25-50% of patients following ablation, of which 21-38% are early recurrences ( 38 ). Some patients still have persistent AF following radiofrequency ablation, and although the traditional drug amiodarone and electrical resuscitation can be used to revert sinus rhythm, the time required for reversion and the need for complex electric shock operations are increasingly unable to meet the treatment needs of patients ( 3 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…33 A recent cost-effectiveness study was conducted evaluating the data produced from the CABANA clinical trial. 34 This study looked at patients over a five-year time period and found higher costs in the ablation group. An important aspect to consider is that this study used intentto-treat cohorts despite very substantial cross-over in the CABANA study.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%